2022
DOI: 10.1039/d2cp01846b
|View full text |Cite
|
Sign up to set email alerts
|

Ba3(BO3)2: the first example of dynamic disorder in a borate crystal

Abstract: Based on ab initio molecular dynamic simulations the dynamic disordering of [BO3] groups in the Ba3(BO3)2 compound has been established. This is the first example of dynamic disordering in borates....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was shown that borates expand sharply anisotropically up to negative areas [18,23]. For the last decade, an overall interest in thermal expansion studies increased sharply [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that borates expand sharply anisotropically up to negative areas [18,23]. For the last decade, an overall interest in thermal expansion studies increased sharply [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%